The value of emotional intelligence for high performance coaching - A commentary - Hanin, J. (International Journal of Sports Science and Coaching, 2011)
For expert performers in high-achievement sport emotional expertise (EE) as a set of skills possessed by an expert in the domain of emotion regulation could be a more appropriate and meaningful term. Coaches` task-related expertise includes such skills as teaching, instructing, preparation, and delivery of successful performance results. Finally, peoplerelated expertise involves, among others, the skills to deal effectively with performance- and communication-related emotions (interpersonal and social competence). The authors` idea to connect task-related skills, leadership skills, and expertise in emotion regulation (in self and others) is well substantiated. Moreover, emotion regulation skills have a special meaning for high-performance coaches who are forced to do their job under conditions of high competitive stress.